Haematological Profile and Seroprevalence of Hepatitis B & C in Patients Referred For Bone Marrow Examination (Medical Forum Monthly, 2024)
Objective: To find out the seroprevalence of hepatitis B and C in patients referred for bone marrow and to study the hematological profile of these patients.Study Design: Descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Department of Pathology, Ayub Medical College Abbottabad from January 2017 to December 2018. Materials and Methods: 1000 consecutive patients recruited by non-random convenience sampling, initially screened by Immunochromatographic Technique (ICT), after history and examination. Patients positive for HBV or HCV, were tested further by Enzyme Linked Immunosorbant Assay (ELISA) for confirmation. ICT positive but ELISA negative patients were advised PCR for confirmation. The confirmed HBV or HCV positive patients were considered for seroprevalence of HBV and HCV. Complete blood counts were done on haematology analyzer, giemsa stained blood film used for microscopic examination of blood & bone marrow. Marrow iron was estimated by pearl stained slides. Data analyzed by SPSS 18.Results: Expressed in tables (1-5), 35 were positive for HBV or HCV, comprising 14 male and 16 females with equal prevalence of HBV in males and females, while hepatitis C more prevalent in females with male: female of 0.78:1, 33.33% patients with hepatitis B and 40% with hepatitis C were >20 years. Anaemia was the commonest (40%) haematological abnormality, followed by thrombocytopenia (23.34%), leucopenia (13.33%), pancytopenia(13.33%) and bicytopenia ( 10% ) respectively. Bone marrow examination revealed increased number of megakaryocytes in 10.8%, lymphocytes in7.7 % and absent marrow iron in 15.7% patients.Conclusion: As much as 3% patients having HBV or HCV had haematological abnormality.